TRANSUMBILICAL LAPAROSCOPIC CHOLECYSTECTOMY VERSUS STANDARD 4-PORT LAPAROSCOPIC CHOLECYSTECTOMY – RESULTS FROM PROSPECTIVE RANDOMIZED TRIAL AND 7 YEARS OF FOLLOW-UP - G. Ganchev; A. Saroglu; A. Julianov (Trakia Journal of Sciences)
PURPOSE: Laparoscopic cholecystectomy is a standard of care for patients with benign gallbladder disease. Recently single-incision techniques gained popularity in order to decrease surgical trauma and to improve cosmetic results and patient satisfaction. The aim of this study is to compare the results of our own modification of transumbilical cholecystectomy versus standard 4-port cholecystectomy in patients with uncomplicated gallstone disease. METHODS: 80 patients (14 male, 66 female) at a mean age of 35±2,5 years (range 18-80) were randomly assigned to either standard 4-port cholecystectomy (n=40) or transumbilical cholecystectomy (n=40). Operative times, intraoperative complications, conversion rate, postoperative complications, pain, vomiting and cosmetic results were compared between two groups. RESULTS: The total mean operative time in the SILC group was 43.63 ± 7.49 min., while in the SLC group it was 37.95 ±8.06 min., (p=0.002). Intraoperative complications and conversions were not recorded in this series. The mean postoperative pain assessed by VAS was: at 6th hour 3.35 (2-5) vs. 3.53 (2-6) (p=0.439), at 24th hour 2.58 (1-4) vs. 2.2 (1-5) (p=0.04), at 48th hour 1.63 (1-3) vs. 1.78 (1-5) (p=0.544). The mean 10-point pain scores for SILC patients at 6 hours was 5.78 (3-9) vs. 6.33 (1-10) in SLC (p=0.161), at 24 hours 4.05 (1-7) vs. 3.58 (1-5) (p=0.122), at 48 hour 2.83 (1-5) vs. 2.4 (1-5) (p=0.093). Postoperative vomiting was observed in 2 (5%) of patients with SILC and 3 (7.5%) of those with SLC by the end of the second hour after surgery. In the early postoperative period up to 72h, no complications were reported. In the late postoperative period up to 7 years 1 (2.5%) operative wound surgery in the area of umbilical incision was reported in the SLC group and the presence of an umbilical hernia in 2 (5%) of patients with SILC. Results of the cosmetic result evaluation at the end of the first month - Body Image Score - mean score of 10.35 ± 1.48 (min. 7, max. 12) for SILC and 10.38 ± 1.41 (min. 6, max. 13) for SLC (p = 0.776). Cosmetic score - mean of the sum of points 20 ± 1,87 (min.17- max. 24) for SILC and 19.08 ± 2,1 (min. 14-max. 23) for SLC (p = 0,577). On a scale of 1 to 10, where 1 is "very ugly" and 10 is "almost imperceptible" (question N8), the mean for patients in the SILC group is 8.3 ± 0.79 (min. 7-max. 10) and at SLC 7.93 ± 0.73 (min. 6-max. 9) (p = 0.125). CONCLUSION: The results of this study demonstrated that both transumbilical cholecystectomy and standard 4-port cholecystectomy are equally safe and effective in the treatment of uncomplicated gallstone disease.